Assessment of inter-individual variability in hamstring muscle recovery after a sport-specific sprint training in women and men - Cosio, Pedro L.; Moreno-Simonet, Lia; Porcelli, Aniello; Lloret, Mario; Padulles, Xavier; Padulles, Josep M.; Farran-Codina, Andreu; Cadefau, Joan A. (Frontiers in Physiology, 2024)
Background: Hamstring muscles are most affected by multiple sprint-based sports as a result of muscle strain during sprinting, leading to reduced performance and increased risk of injury. Therefore, the purpose of the study was to assess inter-individual variability in hamstrings recovery after a sport-specific repeated sprint training (RST), through sprint-specific markers of muscle recovery and associated muscle damage biomarkers in women and men. Methods: Healthy females (n = 14) and males (n = 15) underwent 10 repeated 40-meter sprints with a 3-minute rest pause between each repetition. Force-generating capacity (FGC) by the 90ºhip:20ºknee test and range of motion Jurdan test, together with serum biomarkers [sarcomeric mitochondrial creatine kinase (sMtCK), oxidative stress, irisin] were tested at baseline and 24-, 48-and 72-hours post-exercise through a repeated measures design. Participants were classified according to FGC loss into high responders (HR) and low responders (LR). Results: 21 individuals (10 females, 11 males) were classified as HR (FGC loss > 20% and recovery > 48h), while 8 individuals (4 females, 4 males) were classified as LR. HR individuals showed unrecovered maximal voluntary isometric contraction (MVIC) torque until 72 hours post-training (p = 0.003, np 2 = 0.170), whereas only HR males showed decreased range of motion (p = 0.026, np 2 = 0.116). HR individuals also showed increased sMtCK (p = 0.016, np 2 = 0.128), oxidative stress (p = 0.038, np 2 = 0.106) and irisin (p = 0.019, np 2 = 0.123). Conclusion: There is inter-individual variability in the muscular response to a sport-specific RST, identifiable by MVIC torque assessment. The findings support that the 90ºhip:20ºknee test is a powerful indirect test to screen hamstrings recovery in both women and men, in a cost-effective way. However, the Jurdan test might not be able to monitor hamstrings recovery in sportswomen after RST. Decreases in muscle capacity are linked to damage to muscle sarcolemma and mitochondria until 72 hours post-exercise. Overall, 72 hours will not be adequate time to restore hamstrings structure and function after a sport-specific RST in both female and male responders.